18F-MFBG PET/CT Is an Effective Alternative of 68Ga-DOTATATE PET/CT in the Evaluation of Metastatic Pheochromocytoma and Paraganglioma. (17th January 2023) - Wang, Peipei; Li, Tuo; Cui, Yuying; Zhuang, Hongming; Li, Fang; Tong, Anli; Jing, Hongli
Abstract : Purpose: The current guidelines state that the functional imaging choice in the evaluation of metastatic pheochromocytoma and paraganglioma (PPGL) is 68 Ga-DOTATATE PET/CT. 18 F–meta-fluorobenzylguanidine ( 18 F-MFBG) is a new PET tracer and an analog of meta-iodobenzylguanidine (MIBG). This study aimed to compare 18 F-MFBG and 68 Ga-DOTATATE PET/CT in patients with metastatic PPGL. Patients and Methods: Twenty-eight patients with known metastatic PPGL were prospectively recruited for this study. All patients underwent both 18 F-MFBG and 68 Ga-DOTATATE PET/CT studies within 1 week. Lesion numbers detected were compared between these 2 studies. Results: 18 F-MFBG PET/CT was positive for detecting metastases in all patients, whereas positive results of 68 Ga-DOTATATE PET/CT were in 27 (96.4%) patients. A total of 686 foci of metastatic lesions were detected by both 18 F-MFBG and 68 Ga-DOTATATE imaging. In addition, 33 foci of abnormal activity were only detected by 18 F-MFBG, whereas 16 foci were only shown on 68 Ga-DOTATATE PET/CT. Conclusions: Our data suggest that 18 F-MFBG PET/CT is an effective imaging method in the evaluation of metastatic PPGL and could be alternative of 68 Ga-DOTATATE PET/CT in this clinical setting.